IMPLEMENTASI KEBIJAKAN PENILAIAN KOMPETENSI ASN BERBASIS SISTEM MERIT DI PROVINSI KALIMANTAN TIMUR - Apriani, Fajar; Ningsih, Julia; Pramono, Hoky Dwi; Hilwa, Nur (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Human resources are the main strategic factor in efforts to increase the nation’s competitiveness. Bureaucratic reform in the human resources aspects of the apparatus is carried out through structuring a merit-based human resource management system for the apparatus to realize Good Governance. This research analyzes the successful implementation of the Governor of East Kalimantan Province Regulation Number 14 of 2019 which regulates the existence of the Regional Technical Implementation Unit for Employee Competency Assessment, the Regional Civil Service Agency of East Kalimantan Province in its function of carrying out regional technical personnel activities in the field of employee competency assessment. Through a qualitative approach and the use of interactive analysis, this research describes the findings that the implementation of the competency assessment policy for State Sivil Servant carried out by the Regional Technical Implementation Unit for Employee Competency Assessment, the Regional Civil Service Agency of East Kalimantan Province is in line with the commitment and efforts of the East Kalimantan Provincial Government in implement human resource management policies based on a merit system. This is because there is implementor compliance with the underlying policy so that it is in line with the working procedures of the existing organizational structure, as well as performance or implementation achievements that achieve policy targets, both at the provincial and district/city levels in East Kalimantan. Although until 2022, the Regional Technical Implementation Unit for Employee Competency Assessment facility is still utilized by only a few regional officials and faces limited human resources in carrying out its duties and functions.